Urbanization and Health - Tizón, Jorge L. (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
The article takes as its starting point the recent meeting held in Menorca in September 2011 on «Healthy Urban Planning», sponsored by the International University Menéndez Pelayo and the School of Public Health of Menorca, which together planners, architects planners, sociologists, foresters, representatives of citizens’ movements, active politicians, political alternative, mathematicians, physicians, epidemiologists, psychologists and a psychiatrist. The key idea was that cities are a fundamental building for our species and present data and studies on the «psychodynamic and psychosomatic of urban life». For this reason, and the conflicts that today is subject, should be used to make not only studies and environmental impact assessments and / or ecological urban and territorial plans. We will have to go by requiring previous studies, which have to be agreed between citizens, political representatives and promoters of change, the impact of each of these health plans and health (mental) of citizens and societies.